Anatomical and palynological comparison of three endemic species of Teucrium sect. Teucrium of Turkey - Atasagun, Bayram (Phytotaxa, 2022)
Teucrium ekimii, T. pestalozzae and T. semrae are three endemic species of Turkey belonging to Teucrium sect. Teucrium. These species grow in the western Mediterranean region of the country and are morphologically similar to each other. In the present study, the three species underwent anatomical examination of the stems, leaves and palynological studies for a better characterization of the species and in search of additional diagnostic characters. Quantitative characters were subjected to one-way analysis of variance (ANOVA) and boxplot. In general, these species are anatomically similar, though there are significant differences in stem cuticle thickness, stem epidermis length and width, leaf lower epidermis width and midrib parenchyma width. Pollen grains of all three species are prolate, medium-sized and tricolpate. The exine ornamentation is microverrucate-perforate in T. ekimii, verrucate in T. pestalozzae and microverrucate in T. semrae. Considering palynological characters, polar axis and t (apocolpium) were identified as taxonomically significant characters.